Juridical Review of Notary Deeds Signing which not Performed Simultaneously by Appearing before Notary - Widyo Adi Wicaksono; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
In carrying out the authority, duties and functions of a Notary, as an authentic deed maker, the problem of reading, and signing the parties has been regulated in the Law that regulates . However, in practice, sometimes the parties are unable to attend or cannot attend at the same time because the parties are running urgent business. This study aims to find out the provisions regarding the signing of the deed according to the Notary Position Act, and to find out the legal consequences if the notary deed does not meet the Verlijden principle. The approach method in this research is a normative juridical research method. The method of data analysis using the law is carried out by examining library materials or mere secondary materials. Based on the research, it can be concluded that the implementation of the provisions for signing the deed which is not carried out simultaneously in practice often occurs as long as it is done on the same day, whereas if the day and date of the signing are different, the Notary asks for a power of attorney from parties who are not present by including the contents of the power of attorney.